2020
DOI: 10.3390/ijerph17197078
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Genuineness in Public Engagement—An Exploratory Study of Pediatric Communication on Social Media in China

Abstract: There is a growing need for the public to interact with pediatricians through social media in China, and genuineness is a crucial factor contributing to effective communication, but few studies have examined the relationship between genuineness and its effect on public engagement. This study developed a four-dimension framework including self-disclosure, genuine response, functional interactivity, and genuineness in Chinese culture to investigate the effect of genuineness in the communication of Chinese social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…We can display different varieties of expressions: some intense and sustained, while others are subtle and fleeting (Ambadar et al, 2005 ). One of the most high-level and critical communication features is related to the perception of authenticity of the emotion expressed (Lu et al, 2020 ; Rooney et al, 2012 ). In fact, we can express emotions spontaneously, triggered by real circumstances (i.e., “event-elicited”) (Dawel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can display different varieties of expressions: some intense and sustained, while others are subtle and fleeting (Ambadar et al, 2005 ). One of the most high-level and critical communication features is related to the perception of authenticity of the emotion expressed (Lu et al, 2020 ; Rooney et al, 2012 ). In fact, we can express emotions spontaneously, triggered by real circumstances (i.e., “event-elicited”) (Dawel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Johnston et al, ( 2010 ) showed how genuine (or spontaneous) smiles make perceivers more cooperative than posed smiles. In psychotherapy, therapists’ genuineness, authenticity, and honesty their credibility, which is essential for promoting therapeutic alliance and patients’ trust (Lu et al, 2020 ; Jung et al, 2015 ; Dowell and Berman, 2013 ; Schnellbacher & Leijssen, 2009 ). Furthermore, in movies, the perception of realism in the actor’s performance may promote a more emphatic mechanism and a more emotional contagion of the perceivers (Rooney et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…We can display different varieties of expressions: some intense and sustained, while others are subtle and fleeting (Ambadar et al, 2005). One of the most high level and critical communication features is related to the perception of authenticity of the emotion expressed (Lu et al, 2020;Rooney et al, 2012). In fact, we can express emotions spontaneously, triggered by real circumstances (i.e., "eventelicited") [Dawel et al (2017).…”
mentioning
confidence: 99%
“…For example, Johnston et al (2010) showed how genuine (or spontaneous) smiles make perceivers more cooperative than posed smiles. In psychotherapy, therapists' genuineness, authenticity, and honesty promote to enhance their credibility, which is essential for promoting therapeutic alliance and patients' trust (Dowell and Berman, 2013;Jung et al, 2015;Lu et al, 2020;Schnellbacher and Leijssen, 2009). Furthermore, in movies, the perception of realism in the actor's performance may promote a more emphatic mechanism and a more emotional contagion of the perceivers (Rooney et al, 2012).…”
mentioning
confidence: 99%